2004
DOI: 10.1097/00002820-200411000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Social Cognitive Theory Constructs for Promoting Exercise Among Breast Cancer Patients

Abstract: Physical activity during breast cancer treatment can significantly reduce treatment-related fatigue and improve quality of life. Unfortunately, the majority of women with breast cancer either do not exercise at all or exercise below recommended levels. Little is known about how to enhance physical activity among breast cancer patients. The social cognitive theory, a useful framework for the design of physical activity interventions, has not been studied among breast cancer patients. Our study purpose was to ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
96
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(104 citation statements)
references
References 28 publications
7
96
1
Order By: Relevance
“…The most common barriers to exercise for breast cancer patients in the present study included procrastination, a lack of self-discipline, fatigued by exercise, bra discomfort and exercise not being a priority. Apart from the inclusion of bra discomfort, the barriers to exercise for breast cancer patients in the present study were highly comparable to those previously reported in the literature [23]. It is notable that bra discomfort was the first barrier listed in the present study that can be externally influenced, such as via bra design modifications, making it an ideal option for intervention.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…The most common barriers to exercise for breast cancer patients in the present study included procrastination, a lack of self-discipline, fatigued by exercise, bra discomfort and exercise not being a priority. Apart from the inclusion of bra discomfort, the barriers to exercise for breast cancer patients in the present study were highly comparable to those previously reported in the literature [23]. It is notable that bra discomfort was the first barrier listed in the present study that can be externally influenced, such as via bra design modifications, making it an ideal option for intervention.…”
Section: Discussionsupporting
confidence: 84%
“…. Perceived benefits and barriers to exercise were assessed using an adapted Exercise Benefits and Barriers Scale incorporating barriers identified in the literature to be specific to breast cancer patients [11,20,23,26], and the inclusion of a question regarding exercise bra comfort.…”
Section: Instrumentmentioning
confidence: 99%
See 1 more Smart Citation
“…In terms of favourable attitudes, the majority of cancer survivors appear to be well aware of the potential benefits of engaging in physical activity, and expect physical activity to improve heart/lung functioning, reduce disease risk, build muscle strength, aid weight loss, alleviate stress and improve state of mind (Craike et al, 2011;Rogers et al, 2004Rogers et al, , 2007. Blaney et al (2010) reported that cancer survivors with CRF also recognised that being active is a way of achieving a goal and regaining a sense of normality.…”
Section: Addressing Psychological Barriers To Physical Activitymentioning
confidence: 99%
“…In contrast, motives are autonomous when the behaviour is inherently pleasurable and valued so that the behaviour will be undertaken without the need for external pressure or incentive, and the cause of the behaviour is perceived as internal. The majority of factors which cancer survivors report as motivating are controlling, such as improved physical functioning, aiding recovery from surgery, increasing self-esteem, social contact, improving body image and weight loss, although some survivors also report that they find physical activity relaxing (Blaney et al, 2010;Craike et al, 2011;Rogers et al, 2004Rogers et al, , 2007Schrop et al, 2007).…”
Section: Addressing Psychological Barriers To Physical Activitymentioning
confidence: 99%